IMPLIKASI PERIZINAN BERUSAHA BERBASIS RISIKO TERHADAP EKSPLOITASI SUMBER DAYA ALAM DALAM UPAYA PERCEPATAN INVESTASI DI INDONESIA - Anjar Setiarma; Wilson Tungmiharja; Simona Bustani (Jurnal De Lege Ferenda Trisakti, 2024)
The purpose of writing this journal is to analyze and understand the Government's policy on the Implementation of risk-based business licensing in relation to the exploitation of natural resources in order to accelerate the investment climate in Indonesia. The concept of a permit after the passage of the Job Creation Law is approval from the central government or regional government for the implementation of business activities that must be fulfilled by business actors before carrying out their business activities. The formation of the Job Creation Law using the omnibus law concept is a solution offered by the Government to overcome complex overlapping regulations, including in the field of business licensing in Indonesia so that this effort is expected to encourage domestic investment activities. Risk-based business licensing is currently carried out through the Online Single Submission - Risk Based Approach (OSS-RBA) system, this system is a form of digitalization of public service mechanisms created by the government for business actors. OSS-RBA is expected to provide benefits because business actors can access the system anywhere and anytime, besides that the system is expected to increase and accelerate investment in Indonesia. Through a risk-based licensing concept, it not only makes it easier for investors to enter the Indonesian economic system, but also provides a structured system for the Government to carry out supervision with the aim of preventing misuse of issued permits. By emphasizing on the theory of law as a social engineering tool put forward by Roscoe Pound, Law is not only intended to provide regulation but Regulations provided by Law must be able to shape and create a climate of social life that is desired